2022
DOI: 10.3991/ijet.v17i14.30677
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Learning Resources for University Students During Emergency Remote Learning

Abstract: Although several studies have evaluated online learning tools and resources, few have investigated how useful they are to students. This topic became even more relevant with “emergency remote learning” due to coronavirus disease 2019 (COVID-19). The present study was conducted at a state educational institution in Mexico that offers five university degrees. The objective was to differentiate the importance of online learning resources by degree and by employment status of the students. This quantitative, relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A study by Salas-Pilco, Yang, and Zhang (2022) indicated that students and faculty members need professional training in order to raise the standard of online education, solve internet connectivity issues, and provide students with emotional support. Research by Balderas-Solís, Roque-Hernández, Salazar-Hernández, and Monsivais (2022) looked at how Mexican university students felt about online education. Replies from 909 students were gathered using a survey approach, and the findings showed that several elements of online learning, such class recordings, teacher interactions and online demos, were well received by students, but they also expressed worries regarding projects, assignments, videos and tests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Salas-Pilco, Yang, and Zhang (2022) indicated that students and faculty members need professional training in order to raise the standard of online education, solve internet connectivity issues, and provide students with emotional support. Research by Balderas-Solís, Roque-Hernández, Salazar-Hernández, and Monsivais (2022) looked at how Mexican university students felt about online education. Replies from 909 students were gathered using a survey approach, and the findings showed that several elements of online learning, such class recordings, teacher interactions and online demos, were well received by students, but they also expressed worries regarding projects, assignments, videos and tests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This specific subject has an average population of 10-15 people. After the COVID-19 pandemic [25]- [27] and the petroleum refinery shutdown in Tenerife, an academic activity related to beer brewing was included for the first time in the subject.…”
Section: Potential Implementation Of Brewing Beer Process From Malt E...mentioning
confidence: 99%